Primary breast CD20-positive extranodal NK/T cell lymphoma with stomach involvement: a case report and literature review - Ying Zhang (BMC, 2021)
Abstract Background We present a unique case of primary breast CD20-positive extranodal NK/T cell lymphoma with stomach involvement in a young Chinese female patient. Case presentation The patient presented with a mass in her right breast that rapidly increased in size over approximately 2 months. Upper gastrointestinal endoscopy showed a giant serpentine ulcer in the stomach. Biopsy was performed, and microscopic inspection revealed that the fibrous tissue was diffusely involved by medium to large abnormal lymphocytes. The cytoplasm was low to moderate. The tumor cells had irregular nuclei and inconspicuous nucleoli. The lymphoid cells were strongly immunoreactive to CD20, CD3, CD4, CD56, TIA-1, EBER, and Ki-67 (90%). Epstein-Barr virus genomes were also found in tumor cells by in situ hybridization. A whole-body positron emission tomography (PET)-CT scan revealed intense FDG uptake in the right breast and greater curvature of the stomach. Monoclonal rearrangements of the T cell receptor (TCR-γ) and immunoglobulin heavy chain (IgH) were identified by genetic analysis. Whole-genome next-generation sequencing was performed, and up to 12 gene mutations, including a frameshift mutation in exon 4 of the BCOR (G97Rfs*87; 44.3%) gene and a base substitution mutation (Q61H 17.6%) in exon 3 of the KRAS gene, were detected. Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed using the database for annotation, visualization, and integrated discovery, which showed that rare primary breast CD20-positive extranodal NK/T cell lymphoma had a unique genetic background compared with diffuse large B cell lymphoma and extranodal NK/T cell lymphoma without CD20 expression. The patient received four cycles of the modified SMILE regimen. The second whole-body PET-CT scan revealed that the right breast mass was significantly smaller than before; additionally, FDG uptake in the stomach wall disappeared. Conclusions Systemic examination, extensive immunohistochemistry, and molecular profiling are essential for an accurate diagnosis. More similar cases are required to clarify the biological pathways and even the potential molecular mechanisms of rare lymphomas, which may help direct further treatment.